2016
DOI: 10.1007/s00125-016-4164-4
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise ameliorates dysregulated hippocampal glycometabolism and memory function in a rat model of type 2 diabetes

Abstract: Our findings are the first to describe detailed profiles of glycometabolism in the type 2 diabetic hippocampus and to show that 4 weeks of moderate exercise improves memory dysfunction in type 2 diabetes via amelioration of dysregulated hippocampal glycometabolism. Dysregulated hippocampal lactate-transport-related glycometabolism is a possible aetiology of type-2-diabetes-mediated memory dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…In adult rats, hyperglycemia is associated with increased glycogen concentration and decreased MCT2 protein expression in the hippocampus. 16,17 MCT4 expression is not altered. 16 The effect on GLUT1 seems inconsistent, with some studies reporting upregulation and others finding no alteration.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In adult rats, hyperglycemia is associated with increased glycogen concentration and decreased MCT2 protein expression in the hippocampus. 16,17 MCT4 expression is not altered. 16 The effect on GLUT1 seems inconsistent, with some studies reporting upregulation and others finding no alteration.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, in adult rats, hyperglycemia alters glycogen and lactate metabolism in the hippocampus. 16,17 Astrocytic glycogen breakdown and astrocyte-neuron-lactate transport has an important role in hippocampal synaptic morphology and plasticity. [18][19][20] The objective of the present study was to determine the long-term effects of recurrent neonatal hyperglycemia of graded severity on hippocampal neurochemical profile and dendritic structure in rats.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a rat model of type 2 diabetes (Otsuka Long–Evans Tokushima Fatty rat: OLETF) have been reported to accumulate ~30% higher amounts of glycogen in the hippocampus (Shima et al, ) while brain stem glycogen levels remain similar (Shima, Jesmin, Matsui, Soya, & Soya, ). Another type 2 diabetes model rat strain (Zucker Diabetic Fatty rat: ZDF) was reported to have a tendency for decreased hippocampal glycogen levels (Shima et al, ; Sickmann, Waagepetersen, Schousboe, Benie, & Bouman, ). The streptozotocin (STZ) model of type I diabetes in the rat has been reported to result in modestly higher levels of glycogen (Plaschke & Hoyer, ), whereas magnetic resonance spectroscopic measurement from the occipital lobe of type 1 diabetes patients (Öz et al, ) show a tendency for decreased glycogen amounts.…”
Section: Hippocampal Glycogen Usagesmentioning
confidence: 99%
“…The literature on brain glycogen in diabetes is somewhat confounding. For instance, a rat model of type 2 diabetes (Otsuka Long-Evans Tokushima Fatty rat: OLETF) have been reported to accumulate ~30% higher amounts of glycogen in the hippocampus (Shima et al, 2017) while brain stem glycogen levels remain similar (Shima, Jesmin, Matsui, Soya, & Soya, 2018). Another type 2 diabetes model rat strain (Zucker Diabetic Fatty rat: ZDF) was reported to have a tendency for decreased hippocampal glycogen levels (Shima et al, 2017;Sickmann, Waagepetersen, Schousboe, Benie, & Bouman, 2010).…”
Section: ;mentioning
confidence: 99%
“…Chronic exercise that enhances endurance capacity and cognitive function has also been accompanied with elevated hippocampal glycogen levels in normal rats 16 . In our very recent study, 4 weeks of moderate exercise is effective in improving the declining memory function (hippocampal) in type 2 diabetic rats, and this exercise-induced hippocampal-memory amelioration has been associated with hyper-glycogen levels in the hippocampus 23 . Indeed, recent studies have demonstrated that pharmacological or genetic inhibition of hippocampal glycogen metabolism impairs memory formation and compromises endurance capacity 19 22 , 24 .…”
Section: Introductionmentioning
confidence: 87%